Fibromyalgia 2018
DOI: 10.1136/annrheumdis-2018-eular.7383
|View full text |Cite
|
Sign up to set email alerts
|

AB1067 Prevalence of fibromyalgia in patients with painful knee oa

Abstract: BackgroundFibromyalgia (FM) has been conceptualised as a central nervous system (CNS) disorder, characterised by augmented sensory processing and inability to modulate pain effectively[.1 Global mean prevalence of FM is 2.7% with female/male ratio of 4:1. Several studies highlight the importance of central sensitisation (CS) as a significant manifestation of neuropathic pain symptoms in knee osteoarthritis (OA).2–3 Possible similar mechanisms of chronic pain maintenance in OA – structural pathology, and FM – c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…Fibromyalgia is considered a disease of central sensitization by some [31] and 59 patients in the cohort fulfilled the criteria for fibromyalgia (39% of patients with hand-OA and 52% with PsA).This corresponds with previous observations in PsA cohorts (17% to 64 %) [34,84,142,258,259]. No similar trials have examined the prevalence of patients with hand-OA and concomitant fibromyalgia, but due to the large prevalence of female patients with hand-OA, it is expected that a greater percentage will have concomitant fibromyalgia compared with patients with knee-OA where the prevalence is previously shown to be 10% to 35% [75,115,165]. Patients with fibromyalgia reported higher HAQ and catastrophizing scores than patients without fibromyalgia, a finding which is supported by similar trials in patients with PsA [34].…”
Section: Chapter 4 Discussionsupporting
confidence: 85%
“…Fibromyalgia is considered a disease of central sensitization by some [31] and 59 patients in the cohort fulfilled the criteria for fibromyalgia (39% of patients with hand-OA and 52% with PsA).This corresponds with previous observations in PsA cohorts (17% to 64 %) [34,84,142,258,259]. No similar trials have examined the prevalence of patients with hand-OA and concomitant fibromyalgia, but due to the large prevalence of female patients with hand-OA, it is expected that a greater percentage will have concomitant fibromyalgia compared with patients with knee-OA where the prevalence is previously shown to be 10% to 35% [75,115,165]. Patients with fibromyalgia reported higher HAQ and catastrophizing scores than patients without fibromyalgia, a finding which is supported by similar trials in patients with PsA [34].…”
Section: Chapter 4 Discussionsupporting
confidence: 85%
“…[22][23][24][25] It was observed that fibromyalgia was found in 43.5% of patients with early osteoarthritis. In comparison to this, studies have demonstrated a relatively lower frequency of 6% 26 , 10%, 27 and 22.83% 28 of FM among their OA patients. However, by considering such studies, the cohort was based on established OA while the current study considered the early knee OA patients only.…”
Section: Discussionmentioning
confidence: 80%
“…However, similar results have been shown in the established osteoarthritis patients as compared to early OA patients included as compared to the current study. Bergman et al 27 reported a 56% prevalence of Fibromyalgia in female patients of OA. They too did not segregate the early OA from established OA.…”
Section: Discussionmentioning
confidence: 99%
“…The large variation in prevalence of cFM could be due to difference in detection criteria for fibromyalgia or heterogeneity of patients with PsA (active arthritis, number of female participants etc.). No previous studies have examined the proportion of cFM among patients with hand‐OA, but the prevalence is estimated to be 10% to 35% (Dzekan & Stanislavchuk, 2018; Haliloglu et al, 2014; Mahgoub et al, 2020) in patients with knee‐OA. Greater co‐occurrence in hand‐OA in this study could be anticipated due to the greater number of women affected by hand‐OA or due to participants experiencing at least moderate pain intensity.…”
Section: Discussionmentioning
confidence: 99%